Reversal of Doxorubicin-induced Cardiotoxicity by Using Phytotherapy: A Review - Azar Hosseini; Amirhossein Sahebkar (Korean Pharmacopuncture Institute, 2017)
Doxorubicin as a chemotherapeutic drug is widely used for the treatment of patients with cancer. However, clinical use of this drug is hampered by its cardiotoxicity, which is manifested as electrocardiographic abnormalities, arrhythmias, irreversible degenerative cardiomyopathy and congestive heart failure. The precise mechanisms underlying the cardiotoxicity of doxorubicin are not clear, but impairment of calcium homeostasis, generation of iron complexes, production of oxygen radicals, mitochondrial dysfunction and cell membrane damage have been suggested as potential etiologic factors. Compounds that can neutralize the toxic effect of doxorubicin on cardiac cells without reducing the drug's antitumor activity are needed. In recent years, numerous studies have shown that herbal medicines and bioactive phytochemicals can serve as effective add-on therapies to reduce the cardiotoxic effects of doxorubicin. This review describes different phytochemicals and herbal products that have been shown to counterbalance doxorubicin-induced cardiotoxicity.